Survey of Reserves Reactions to the GDP Per Capita in Ghana - Yeboah, Benjamin; Adoma-Worae, Thomas; Yeboah, Michael; Ofori, Debrah (The Journal of Accounting and Management, 2022)
This study provides empirical evidence for determining the benefits of reserves, including gold in supporting the Gross Domestic Product (GDP) per capita in Ghana period between 1960 and 2019. This study aims is to ascertain the undulating trend tendencies of financial vulnerability in reserve management and estimate the extent of reserve benefits that persist to increase GDP per capita earnings using the Markov switching model. This study uses the Makov switching model as an estimator of the undulating trend propensities and persists the benefits of reserves to the earnings of GDP per capita in Ghana. The study obtained data from the 2019 World Development Indicators of the World Bank. The results reveal that reserve benefits are more persistent in regime 1, with positive significance at the 1% level, achieving higher scores of both 50th and 75th percentiles and lower variance scores. Howeve r, the result for regime 2 do not support sufficient benefits to the earnings of GDP per capita. A better explanatory model should identify other factors to test the estimation for future research. The study will be encouraged to expand the sample to cover more countries in Sub-Saharan Africa, by using existing empirical archival data. This study empirically tests the evidence of persistent reserve benefits to GDP per capita in Ghana’s context which can have resemblance lessons on other African countries using the Markov switching model.